(untitled) (Texas Journal of Engineering and Technology, 2023)
This article explores the impact of lactose on the human body, focusing on lactose intolerance, a common digestive disorder. Lactose is a natural sugar found in dairy products, and its digestion relies on the enzyme lactase. The keywords for this study include lactose, lactose, lactose intolerance, dairy products, and digestive disorders. The discussion section highlights the significance of this condition and its dietary implications. In conclusion, we provide suggestions for individuals with lactose intolerance and offer insights into potential areas for future research